Prevalence of anaemia among school going adolescent girls in Bardiya, Nepal: Evidence from a public health screening program - Prasad Chaudhary, Narayan; Poudel, Swastika; Paudel, Sandesh (Journal of Chitwan Medical College, 2026)
Introduction: Anaemia remains a substantial challenge among adolescent girls in Nepal, resulting in poor physical growth, cognitive impairment, and adverse reproductive health outcomes. This study aimed to determine the prevalence and risk factors associated with anaemia among school-going adolescent girls in Bardiya, Nepal. Methods: A retrospective cross-sectional study based on secondary data was conducted using data collected during a district-wide anaemia screening program implemented in government schools across Bardiya, Lumbini Province, from 05 Jun 2025 to 29 Jun 2025. Haemoglobin levels were assessed using the cyanmethemoglobin method. Socio-demographic, anthropometric, and menstruation-related data were collected using a Kobo tool and register. Bivariate analysis using Chi-square tests was performed to identify factors associated with anaemia, statistical significance was set at a p-value <0.05 with a 95% confidence interval. Result: Among 3,334 adolescent girls screened, the prevalence of anaemia was common (80.2%), with mild anaemia 36.1%, moderate 42.4%, and severe 1.8%. of cases. Older (15-19 y) adolescent girls (OR=1.34, p=0.003), from the Tharu ethnic group (OR=3.53, p<0.001), were significantly more likely to be anaemic. Adolescent girls who had taken iron-folic acid tablets (OR=0.46, p <0.001) were significantly less likely to be anaemic. Conclusions: The prevalence of anaemia among school-going adolescents is alarmingly high. Age, ethnicity, and IFA intake were found to be associated with anaemia. These findings highlight the importance of context-specific interventions, focussing on dietary practices, health education, and adherence to supplementation programs. Focussed measures are needed to address anaemia among adolescents, especially in marginalised ethnic groups.